State-Owned Enterprises in Emerging Europe : The Good, the Bad, and the Ugly - Bower, Uwe (IMF Working Papers; Working Paper ;, 2017)
State-owned enterprises (SOEs) play an important role in Emerging Europe's economies, notably in the energy and transport sectors. Based on a new firm-level dataset, this paper reviews the SOE landscape, assesses SOE performance across countries and vis-a-vis private firms, and evaluates recent SOE governance reform experience in 11 Emerging European countries, as well as Sweden as a benchmark. Profitability and efficiency of resource allocation of SOEs lag those of private firms in most sectors, with substantial cross-country variation. Poor SOE performance raises three main risks: large and risky contingent liabilities could stretch public finances; sizeable state ownership of banks coupled with poor governance could threaten financial stability; and negative productivity spillovers could affect the economy at large. SOE governance frameworks are partly weak and should be strengthened along three lines: fleshing out a consistent ownership policy; giving teeth to financial oversight; and making SOE boards more professional.